Study on change of color and some properties of high density polyethylene/organo-modified calcium carbonate composites exposed naturally at Dong Hoi-Quang Binh - Minh, Le Duc; Chinh, Nguyen Thuy; Giang, Nguyen Vu; Le, Tong Cam; Kim Quyen, Dau Thi; Giang, Le Duc; Hoang, Thai (Vietnam Journal of Chemistry, 2017)
This paper presents the study on the UV-Vis spectra, change of color and some properties of high density polyethylene/organo-modified calcium carbonate (HDPE/m-CaCO3) composites exposed naturally in Dong Hoi district, Quang Binh province (Vietnam). From June 2014 to June 2016, the samples of HDPE/m-CaCO3 composites were tested naturally on outdoor shelves at Dong Hoi sea atmosphere region (at Dong Hoi, Quang Binh). The change of UV-VIS spectra, color and some properties of the HDPE/m-CaCO3 composites depend on geographic, weather and climatic factors (solar radiation, temperature, humidity, etc.). In the UV-VIS spectra, the band at 265 nm showed the formation of the carbonyl groups such as ketone, lactone carbonyl and aliphatic ester which were occurred in photo-degradation process of HDPE/m-CaCO3 composites. The results of color change indicated the surface of the samples of HDPE/m-CaCO3 composites was lightened continuously with increasing natural exposure time and increased in total color difference value and significant loss in both redness and yellowness. Da*, Db* values and electrical breakdown of HDPE/m-CaCO3 composites were decreased while their Dl*, DE, dielectric constant and dielectric loss were increased with rising natural exposure time. Dielectric constant of HDPE/m-CaCO3 composites was in the range of 1.75 to 2.1 and dielectric loss of HDPE/m-CaCO3 composites went up from 1.7 to 3.2 for 0 to 24 months. The electrical breakdown of HDPE/m-CaCO3 composites reduced due to the decrease in the relative crystalline degree of the samples caused by the scission photo-degradation of HDPE macromolecules in HDPE/m-CaCO3 composites for natural exposure time. Keywords. HDPE/CaCO3 composites, photo-degradation, natural exposure, color change, electric properties, UV-Vis spectroscopy.